2018
DOI: 10.15252/embr.201745335
|View full text |Cite
|
Sign up to set email alerts
|

RNase H eliminates R‐loops that disrupt DNA replication but is nonessential for efficient DSB repair

Abstract: In , genome stability depends on RNases H1 and H2, which remove ribonucleotides from DNA and eliminate RNA-DNA hybrids (R-loops). In, RNase H enzymes were reported to process RNA-DNA hybrids produced at a double-strand break (DSB) generated by I-PpoI meganuclease. However, it is unclear if RNase H is generally required for efficient DSB repair in fission yeast, or whether it has other genome protection roles. Here, we show that cells, which lack the RNase H enzymes, accumulate R-loops and activate DNA damage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 68 publications
(118 reference statements)
4
52
0
Order By: Relevance
“…The exact mechanism by which these proteins function is not fully understood; however, it is becoming clear that they are acting upon RNA molecules at break sites. There is substantial evidence implicating RNA molecules in DNA repair, and several publications have now corroborated the generation of DNA:RNA hybrids (R-loops) at DSBs and importantly demonstrated that these structures are required for efficient DSB repair [18][19][20][21][22][23][24][25][26][27][28] . Interestingly, many RBPs are implicated to function via these DSB-induced Rloops, for example, Drosha has been shown to be required for their generation and RNase H2 and Senataxin for their resolution 19,21,24 .…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism by which these proteins function is not fully understood; however, it is becoming clear that they are acting upon RNA molecules at break sites. There is substantial evidence implicating RNA molecules in DNA repair, and several publications have now corroborated the generation of DNA:RNA hybrids (R-loops) at DSBs and importantly demonstrated that these structures are required for efficient DSB repair [18][19][20][21][22][23][24][25][26][27][28] . Interestingly, many RBPs are implicated to function via these DSB-induced Rloops, for example, Drosha has been shown to be required for their generation and RNase H2 and Senataxin for their resolution 19,21,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps even more important is the fact that the system produces one-ended DSBs which more accurately resemble the type of substrates resulting from collapsed replication forks [136]. Using wild type cells or several mating type defective mutants ( Figure 5B) [130,137,138] the role of various DNA damage response genes have been investigated [136,139,140]. Work has also led to the identification of several recombination and replication genes, particularly the swi (switching) genes [117,118,141,142].…”
Section: Mating Type Loci Serve As a Natural Site For Studying Collapmentioning
confidence: 99%
“…Nonetheless, mice expressing mutant RNASEH2A and RNASEH2B alleles show that these mutations result in the direct accumulation of nucleic acids that induce IFN through cGAS/STING signaling (Mackenzie et al, 2016; Pokatayev et al, 2016). Evidence suggests that the specific origin of nucleic acids that leads to RNase H2-mediated inflammatory disease may occur through DNA damage responses as well as recognition of retroelements (Bartsch et al, 2017, 2018; Günther et al, 2015; Zhao et al, 2018). Furthermore, two recent studies have also shown that DNA damage leading to the formation of micronuclei induces an IFN response through cGAS and that this occurs in frequently in the absence of RNASEH2B (Harding et al, 2017; Mackenzie et al, 2017).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%